Impulsive and compulsive behaviors can be induced by opposite GABAergic dysfunctions inside the primate ventral pallidum - Saga, Yosuke; Galineau, Laurent; Tremblay, Léon (Frontiers in Systems Neuroscience, 2022)
The ventral pallidum (VP) is central in the limbic Basal Ganglia circuit, controlling both appetitive (approach) and aversive (avoidance) motivated behaviors. Nevertheless, VP involvement in pathological aspects remains unclear, especially in the behavioral expression of different motivational dysfunctions. This study aimed to investigate how the VP contributes to the expression of abnormal behaviors via opposite GABAergic dysfunctions. Opposite GABAergic dysfunctions were induced by injecting muscimol (a GABAA agonist) and bicuculline (a GABAA antagonist) into monkeys. We determined the effects of both substances on self-initiated behaviors in lab-chair and in free-moving home-cage contexts in six monkeys, and in two animals performing an approach-avoidance task in appetitive and aversive contexts. While the self-initiated behaviors induced by bicuculline injections in VP were characterized by compulsive behaviors such as repetitive grooming and self-biting, muscimol injections induced impulsive behaviors including limb movements in a lab-chair context and exploration behaviors in a free-moving context. More specific behavioral effects were observed in the approach-avoidance task. The muscimol injections induced premature responses and erroneous screen touches, which characterize impulsive and attention disorders, while the bicuculline injections into the VP increased passive avoidance (non-initiated action) and task-escape in an aversive context, suggesting an anxiety disorder. These results show that activating or blocking GABAergic transmission in the VP impairs motivated behaviors. Furthermore, the behavioral expressions produced by these opposite disturbances show that the VP could be involved in anxiety-driven compulsive disorders, such as OCD, as well as in impulsive disorders motivated by attention deficits or reward-seeking, as seen in ADHD or impulse control disorders.